2016
DOI: 10.1038/ncomms13164
|View full text |Cite
|
Sign up to set email alerts
|

Platinum recycling going green via induced surface potential alteration enabling fast and efficient dissolution

Abstract: The recycling of precious metals, for example, platinum, is an essential aspect of sustainability for the modern industry and energy sectors. However, due to its resistance to corrosion, platinum-leaching techniques rely on high reagent consumption and hazardous processes, for example, boiling aqua regia; a mixture of concentrated nitric and hydrochloric acid. Here we demonstrate that complete dissolution of metallic platinum can be achieved by induced surface potential alteration, an ‘electrode-less' process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 40 publications
3
57
0
Order By: Relevance
“…Hodnik et al. demonstrated an effective process that included alternation of purging ozone and carbon monoxide in mild acidic solution …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hodnik et al. demonstrated an effective process that included alternation of purging ozone and carbon monoxide in mild acidic solution …”
Section: Introductionmentioning
confidence: 99%
“…demonstrated an effective processt hat included alternation of purging ozone and carbonm onoxide in mild acidic solution. [37] During the potentiodynamic dissolution process controlled by using an externalp otential (Figure 1a,b), dissolved platinum can redeposit through awell-known process (Ostwald ripening) where larger particles grow on accounto ft he smaller ones. [16,25,38,39] This leads to significant growth of the Pt nanoparticles, which reduces the efficiency of the dissolution process.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Those studies have revealed that Pt electrochemical dissolution is predominantly a transient phenomenon occurring due to an interplay of Pt oxidation and reduction. The amount of dissolved platinum can be manipulated via different electrochemical treatments (scan rate, width of anodic and cathodic potential window), 1 gas atmosphere, 12 electrolyte, presence of organic molecules, 6,13 alloying metals, 8,14,15 thickness of the catalyst layer, 10,16 type of support material 16 and, last but not least, by the Pt particle size. 4 Much is owed to the development of advanced on-line analytical tools, especially electrochemical scanning flow cell (SFC) in combination with inductively coupled plasma mass spectrometer (ICP-MS).…”
mentioning
confidence: 99%
“…This should be considered as a drawback since many relevant environments where metals are key components, such as capacitors, sensors, electrochemical reactors, and batteries operate in pure organic or a mixture of organic and aqueous phases. Furthermore, understanding the corrosion of noble metals has started to emerge as an important issue from the perspective of environmentally friendly recycling strategies, 16 where organic solvents show much promise. [17][18][19][20] ICP-MS analysis of organic matrices is not as common as in case of aqueous matrices and presents a much greater challenge in tackling instrumental settings and several unusual spectral interferences.…”
Section: Introductionmentioning
confidence: 99%